Atoms and bits - García Amen, Mg. Arq. Fernando (Universidad Nacional del Litoral, 2018)
This paper intends to reflect, from an academic point of view, on the potential of digital fabrication as a technique but also as a way of thinking and conceiving the architectural project in the begining of the fourth industrial revolution. It also focuses on latin-american scenario and its development opportunities in a new disruptive technological context. The main goal of this paper is to contribute to the understanding of this new paradigm which is in permanent evolution, and also to add a brick to the theoretical platform that supports the study of new digital phenomenom.